The (in)visibility of Human Rights in Physical Education bachelor courses at Brazilian federal universities - Palmeira, Lana Lisiêr de Lima; Cordeiro, Carla Priscilla Barbosa Santos; Prado, Antonio Gottschlisch do; Prado, Edna Cristina do (Brazilian journal of physical education and sport, 2021)
This article investigated the Physical Education teachers’ preparation aiming to understand whether the Human Rights Education’s components are included in this preparation and, if present, how satisfactorily is in the sense of not only training people capable only of technical knowledge and skills, but we also seek to forge them completely, making them subjects of rights in the broadest sense of the word. From a qualitative approach in based on the Content Analysis, it discusses fundamental concepts of Education in Human Rights and the recommendations from the National Curriculum Guidelines which regulates Physical Educationundergrad coursed to undertake the analysis of political pedagogical projects and the curriculum of such undergraduate courses oﬀered at Brazilian federal universities. The results revealed the subordination of the humanistic elements compared to technical contents. The conclusion of the study reinforces the need for more research on this topic and the conviction that, somehow, the reﬂection presented can contribute to deep discussion that may feedback the humanism in university ambivalence.